South Africa in world development: Prospects for a human economy (Respond to this article at http://www.therai.org.uk/at/debate). Issue 6 (25th November 2014) - Sharp, John; Hart, Keith; Laterza, Vito
Abstract : South Africa was once notorious for an extreme system of racial inequality known as apartheid. It is still a world leader in economic inequality, but the racial situation is confused. In the meantime something like apartheid has become universal. The Southern African regional economy has some features that point to a more humane alternative to unequal society, to a "human economy". The world needs a new free trade movement that would begin to dismantle the institutions of national privilege and insist on movement as a human right.